Enhanced thermal conductivity of cooling liquid using nano material's - Kheria M.Essa; Hashim Zydan Mohammed (Engineering and Technology Journal, 2015)
In present work alumina with grain size (50nm )and titanium dioxide with grain size (20nm ) are used tothermal conductivity is tested separately when mixed with water at different percent concentrations (0.05%, 0.1 %, 0.3%, and 0.5 W %),in order to investigate their effects on enhancement of heat transfer of pool boiling water and enhancement thermal conductivity of nanofluid. The experimental results of thermal conductivity of water before and after adding of nanoparticles have been presented in this work. The results of a theoretical study of thermal conductivity of nanofluids with Al2O3 and TiO2 nanoparticles are also presented and compared with the experimental results. Both results showed an increment of 1.5% -1.8% enhancementshave been obtained when a small amount of nanoparticles is added to the pure water. The theoretical calculation is based on the mechanism of Brownian motion which is the reason for improvement of thermal conductivity.